Pharmacological mechanisms of berberine against triple negative breast cancer: Integration of network pharmacology and experimental validation - Tian Qin; Kaixuan Liu; Yushi Yang; Jinjin Huang; Tengxiang Chen; Yinhui Jiang; Shu Xu (Phytomedicine Plus)
Objective: Berberine (BBR) has garnered attention for its potential effectiveness against triple-negative breast cancer (TNBC). To further understand its pharmacological mechanisms, this study employed a combination of network pharmacology analysis and experimental verification for providing insights into the potential of BBR as a therapeutic option for TNBC. Methods: Through an application of network pharmacology methods to foresee the essential targets and pathways of BBR in countering TNBC, an analysis of the protein-protein interaction (PPI) network, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways was carried out. The confirmation of the bond between BBR and the target sites occurred via molecular docking utilizing CavityPlus and Autodock vina. To validate the outcomes of the network pharmacology analysis, experimental verification was performed through in vitro experiments. Results: By searching the overlap between BBR and TNBC targets, a total of 257 potential targets were retrieved. PPI network analysis revealed that top of 15 targets as the pivotal gene. In the analysis of gene ontology (GO) enrichment results of effective target GO functional enrichment analysis suggested that BBR may be involved in protein phosphorylation and anti-apoptotic biological processes. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated that the anti-cancer effect of BBR was mediated by multiple pathways, such as pathways in cancer signaling pathways and apoptosis signaling pathways. The ''Compound-target-GO-pathway-disease'' network constructed and acetylation targets with molecular docking demonstrated the regulation of acetylation by BBR. Subsequently, in vitro assay results indicated that BBR, as an inhibitor of deacetyltransferase (KDACi), was capable of inhibiting the proliferation and migration of MDA-MB-231 cells and inducing cell apoptosis. Conclusion: Through combining network pharmacology with vitro validation, this study identified BBR as a potential target of KDACi in TNBC, providing new insights into the pharmacology of acetylation in the treatment of TNBC.